Research on the impact mechanism of digital technology on the new-quality productivity of port logistics - Kebiao Yuan; Zhijian Xu; Haiwei Fu (PLoS ONE, 2025)
The development of port digital technology is an important way to promote the development of new-quality productivity in port logistics. This study takes Ningbo Port, Shanghai Port, and Tangshan Port as the research objects, and selects the data from 2013–2023 to explore the inner mechanism of the impact of digital technology on the new-quality productivity of port logistics. The results show that digital technology has a significant positive impact on the new quality productivity of port logistics, and the conclusions remain robust after the endogeneity test of the results using the instrumental variables method, eliminating the data of abnormal years, adding fixed effects, and adopting the instrumental variables method. The mechanism test shows that digital technology affects the level of the new quality productivity of port logistics by facilitating the development of new types of digital infrastructures. The digital economy also plays a mediating role between digital technology and the new-quality productivity of port logistics. The findings of the study not only provide key clues to accurately grasp the connotation and characteristics of new productivity in port logistics but also further expand and deepen the breadth and depth of theoretical and empirical studies on the development of digital technology and new-quality productivity in port logistics.